Cardiac rehabilitation after myocardial infarction - role, goals and effects - Misiło, Adriana; Olczyk, Krzysztof; Sosna, Monika; Mordoń, Krzysztof (Journal of Education, Health and Sport, 2023)
Cardiovascular diseases, in particular ischemic heart disease, are the leading cause of death worldwide. According to the current guidelines of scientific societies, the most important target group, in which preventive actions play a key role, are e.g. patients with ischemic heart disease. The actions taken aimed at slowing down the progression of the disease, optimizing therapy, including its individualization, education and counseling in the field of pro-health behaviors. Preventive measures are also cost-effective in relation to the costs incurred for a number of measures taken in the event of an acute cardiovascular event. As a result, comprehensive care programs with secondary prevention as the primary objective are now considered the standard of care, particularly in patients with acute coronary artery disease (ACS).